STUDY OF POTENTIAL AND DEVELOPMENT STRATEGY OF MANGROVE ECOTOURISM IN SUNGAI ASAM VILLAGE INDRAGIRI HILIR REGENCY RIAU PROVINCE - Kaprisal, Kaprisal; Tanjung, Afrizal; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK Mangrove ecotourism is one of efforts to maintain and utilize mangrove forests sustainably. This research was conducted in May 2017 in Sungai Asam Village, Reteh district, Indragiri Hilir Regency, Riau Province. This study was aimed to determine the potential of mangrove ecosystems, to know the level of participation and perception of policy makers (community and stakeholders), and to compose strategies for developing mangrove ecotourism in Sungai Asam Village. The method used in this research was survey method. Sampling point and respondents determined by purposive sampling method. Sungai Asam Village has the potential to be developed as a mangrove ecotourism area due to the good ecological condition of the forest. Community participation in ecotourism development in Sungai Asam village is low with IPR value of -0.16 and mean value of 0.95, while community perception on ecotourism development in Sungai Asam village is high with IPR value of -2.68 and the mean value of 7.63. Based on the perception of the stakeholders that the mangrove forest area of Sungai Asam Village is suitable to be a mangrove ecotourism area. The strategy that must be applied in the development of mangrove ecotourism in Sungai Asam Village is to implement aggressive strategy (Growth Oriented Strategy) by prioritizing the SO Strategy those are: 1) determining the mangrove forest area of Sungai Asam Village as a conservation area, 2) Creating a general management plan, 3) Building cooperation with colleges or research institutes 4) Developing local communities. Keyword: Potentional Study, Development Strategy, Ecotourism, Mangrove, Participation, Perception.